Comparison of Functional Recovery in the Very Early Period After Surgery Between Plate and Nail Fixation for Correction of Stable Femoral Intertrochanteric Fractures: A Controlled Clinical Trial of 18 Patients. (June 2014) - Yamauchi, Koun; Fushimi, Kazunari; Shirai, Goshi; Fukuta, Masashi
Purpose: This study aimed to compare the differences in functional recovery between patients undergoing plate and nail fixation in the very early period after surgery. Method: This study was designed as a controlled clinical trial that included 18 patients who were surgically treated with either dynamic hip screw as plate fixation or proximal femoral nail as nail fixation for stable intertrochanteric fractures. In particular, all patients selected for the study reported walking completely independently without the use of walking aids prior to sustaining their initial fracture. In all, 8 patients (mean age, 73.8 years; range, 65-89 years) were treated with plate fixation (group plate) and 10 patients (mean age, 79.7 years; range, 70-90 years) were treated with nail fixation (group nail). Functional evaluations were assessed every week after surgery using the Japanese Orthopaedic Association (JOA) hip functional scores and active range of motion (ROM) of the hip joint. Results: The recovery of activities of daily living (ADLs) according to JOA hip functional scores at week 4 after surgery was significantly better in group nail than in group plate ( P = .03), whereas active ROM of hip flexion improved significantly in group plate than in group nail at weeks 3 and 4 after surgery ( P = .04 and P = .02, respectively). Conclusions: The results suggested that nail fixation may provide a more rapid recovery of ADLs than that of plate fixation in the very early period after surgery. However, plate fixation may provide better ROM of hip flexion than that of nail fixation.